1981
DOI: 10.1523/jneurosci.01-04-00358.1981
|View full text |Cite
|
Sign up to set email alerts
|

Opioid and non-opioid stress analgesia: assessment of tolerance and cross-tolerance with morphine

Abstract: Opioid and non-opioid mechanisms of analgesia elicited by two kinds of footshock stress that differ only in temporal characteristics previously have been inferred on the basis of susceptibility to naloxone blockade. The present study sought further evidence on this point by comparing these two kinds of footshock analgesia for possible tolerance development and cross-tolerance with morphine. It was found that, with repeated exposure to stress, tolerance developed to naloxone-sensitive, but not naloxone-insensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
3

Year Published

1982
1982
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(79 citation statements)
references
References 15 publications
8
68
3
Order By: Relevance
“…Repeated once-daily exposure to intermittent footshock stress for two weeks results in tolerance to an opioid-dependent, but not an opioid-independent, form of stress antinociception (Lewis et al, 1981;Terman et al, 1986). Similarly, we showed that chronic treatment with the cannabinoid agonist WIN55,212-2 attenuated endocannabinoid-mediated stress antinociception .…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…Repeated once-daily exposure to intermittent footshock stress for two weeks results in tolerance to an opioid-dependent, but not an opioid-independent, form of stress antinociception (Lewis et al, 1981;Terman et al, 1986). Similarly, we showed that chronic treatment with the cannabinoid agonist WIN55,212-2 attenuated endocannabinoid-mediated stress antinociception .…”
Section: Introductionsupporting
confidence: 60%
“…Repeated once daily exposure to intermittent footshock stress (20 min at 0.2 Hz × 14 days) induces tolerance to opioid-mediated stress antinociception (Lewis et al, 1981;Terman et al, 1986). Thus, it is noteworthy that repeated daily exposure to brief, continuous footshock stress (3 min × 15 days) does not induce tolerance to opioid-mediated stress antinociception (Lewis et al, 1981;Terman et al, 1986) and produced no deficit in endocannabinoid-mediated stress antinociception in our study. Moreover, WIN55,212-2 produced similar antinociceptive effects in rats exposed repeatedly to the footshock stressor and rats not subjected to footshock.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Further, an increase in the toradiography in discrete regions of the brain of arthritic rats, activity of serotoninergic networks may underlie the potentiated such as the periaqueductal gray, stimulation of which elicits the antinociceptive action of morphine induced by acute stress (Kelly and Franklin, 1984). In analogy to arthritis, other models of chronic pain (footshock or mechanical stimulation) evoke an increased antinociceptive response to morphine (Lewis et al, 1981;Appelbaum and Holtzman, 1984;Sherman et al, 1984;Williams et al, 1984;Girardot and Holloway, 1985). It has been contended that this may reflect classical conditioning; that is, cues associated with exposure to stress summate with morphine to produce an enhanced antinociception.…”
Section: Endogenous and Exogenous Opioid Control Of Nociception In Armentioning
confidence: 99%
“…Subsequent one-way ANOVA followed by Fisher's PLSD indicated that significant tolerance developed at 30 min post-injection ("morphine" < "saline"; F3,28=6.6; p<0.05) but not at later time points (p>0.05). The shorter lasting analgesia (and subsequently, tolerance) compared to Figure 1 could be due to a combination of both a lower challenge dose used in this experiment (5 mg/kg versus 7.5 mg/kg, s.c.) and cross-tolerance of stress-induced analgesia across all groups (Lewis et al 1981) because this regimen required three times as many injections and concomitant handling. Co-administration of MK-801 with morphine completely blocked the development of morphine tolerance exhibited at 30 min in the 129S6/ SvEv strain as these mice demonstrated significantly greater analgesia than morphine-tolerant mice (p<0.05) but did not differ from control mice (p>0.05) ( Figure 3A).…”
Section: Resultsmentioning
confidence: 99%